The importance of the Kazakh Steppe in the cross-border trade of the China and Russian Empire in the second half of the 19th – early 20th century - Alimdjanov, Bakhtiyor A.; Nurbayev, Zhaslan E.; Sultangazy, Gulmira Zh. (Journal of the Belarusian State University. History, 2025)
Based on unpublished archival documents, data from commercial banks and biographies of merchants and bais, the article examines the development of trade on the border between the Kazakh Steppe, China and the Russian Empire in the second half of the 19th – early 20th century. In historical literature, the situation on this border is characterised as modernising and combining features of imperial and colonial policies. It is argued that imperial rather than colonial policy was pursued on the border of East Turkestan, since the region was not under control and there was no pressure on local merchants and border populations. Passive intervention by the imperial administration in cross-border trade brought certain benefits to political players and ensured a loyal attitude from local trade structures. The above-mentioned border recorded the political ambitions of China and Russia without having a significant impact on cross-border trade, which contributed to the growth of entrepreneurship on both sides. This situation changed the steppe region of Kazakhstan in social-economic terms, namely, it transformed the traditional structure of Kazakh society (new social categories such as bais and Kazakh merchants appeared) and internal trade. Imperial policy led to the growing role of border towns (Verny, Kashgar, Kuldja, Orenburg and Tashkent) in trade.